Mechanical properties and in vitro cytocompatibility of dense and porous Ti–6Al–4V ELI manufactured by selective laser melting technology for biomedical applications. (November 2021) - Suresh, Santhosh; Sun, Chen-Nan; Tekumalla, Sravya; Rosa, Vinicius; Ling Nai, Sharon Mui; Wong, Raymond Chung Wen
Abstract: The Ti–6Al–4V alloy is the most common biomaterial used for bone replacements and reconstructions. Despite its advantages, the Ti–6Al–4V has a high stiffness that can cause stress-shielding. In this work, we demonstrated that the selective laser melting (SLM) technology could be used to fabricate porosity in Ti–6Al–4V extra low interstitial (ELI) to reduce its stiffness while improving cell adhesion and proliferation. With a porosity of 14.04%, the elastic modulus of the porous Ti–6Al–4V ELI was reduced to 80 GPa. The compressive stress and the 3-point-bending flexural tests revealed that the porous Ti–6Al–4V ELI possessed a brittle characteristic. The additional pores within the beams of the lattice structures of porous Ti–6Al–4V ELI increased its surface arithmetic average roughness, Ra = 3.94 μm. The in vitro cytocompatibility test showed that the SLM printing process and the post-processes did not cause any toxicity in the MC3T3-E1 cells. The in vitro cell proliferation test also showed that the porous Ti–6Al–4V ELI increased the proliferation rate of osteogenic induced MC3T3-E1 cells on Day 7. The findings from this study would provide engineers and researchers with both the mechanical information and biological understanding of SLM printed porous Ti–6Al–4V ELI, and SLM printed dense Ti–6Al–4V ELI towards biomedical applications. Graphical abstract: Image 1 Highlights: Ti–6Al–4V ELI manufactured by selective laser melting technology was not cytotoxic. Porous Ti–6Al–4V ELI enhanced cells adhesion and proliferation. Introduction of hexagonal lattice structures reduced the elastic modulus of Ti–6Al–4V ELI. Dense printed Ti–6Al–4V ELI showed 99.05% density.